The phonetic interaction of stress and intonation: a study of Standard Lithuanian - Švageris, Evaldas (Vilnius University Open Series, 2022)
It is commonly accepted, that word stress in Standard Lithuanian has a complex phonetic nature. However, empirical data do not support such a view. The functional importance of acoustic parameters can only be proven relying on their “relations of relations” between stressed and unstressed syllables. To put it simply, we cannot state for sure that in all cases stressed syllables are superior in acoustical means. We can rely on intersyllabic relation of some sort only. If this is true, word stress is no more recognizable from a sintagmatic point of view. In addition, such interpretation presupposes a very complex mechanism of stress perception that is difficult to verify by experimental means. This article highlights the phonetic interaction of prosodic elements in the hope that more invariant features of acoustic stress structure can be captured from this perspective. The analyzed data show that prosodic elements selectively regulate the amount of acoustic energy, its degree of variation and dynamics. The first two are the prerogative of the phrasal intonation and the third is determined by the stress. The latter prosodic element, to put it more simply, is a factor that determines the control of acoustic energy distribution at the intersyllabic level.